An Implicit Algorithm for Finding a Fixed Point of a Q-Nonexpansive Mapping in Locally Convex Spaces. (13th August 2021) - Soori, E.; Omidi, M.R.; Farajzadeh, A.P.; Wang, Yuanheng
Abstract : In this paper, the notion of the q -duality mappings in locally convex spaces is introduced. An implicit method for finding a fixed point of a Q -nonexpansive mapping is provided. Finally, the convergence of the proposed implicit scheme is investigated. Some examples in order to illustrate of the main results are presented.